"Joining the dots" for patients with systemic lupus erythematosus: personal perspectives of health care from a qualitative study. Issue 5 (11th October 2005) - Hale, E D; Treharne, G J; Lyons, A C; Norton, Y; Mole, S; Mitton, D L; Douglas, K M J; Erb, N; Kitas, G D
Abstract : Objectives: To examine the perceptions of patients with systemic lupus erythematosus (SLE) about their health care provision in the United Kingdom. Methods: Semistructured interviews were conducted with 10 women aged 26 to 68 years who were diagnosed with SLE one to 12 years earlier. Interviews were audio recorded, transcribed verbatim, and analysed using interpretative phenomenological analysis to organise the themes of importance to participants. Results: Four themes emerged: diagnostic difficulties; understanding; communication; and integrated health care. Before diagnosis there was concern to appear legitimately ill and to have a label for the condition. After diagnosis participants still encountered health care professionals who were poorly informed about SLE. Family, friends, and employers did not understand the fluctuating nature of SLE, which often led to isolation. Participants felt that even health care professionals who specialised in SLE could not fully understand the psychosocial impact of the condition, and therefore did not provide information to meet those needs. Participants did not know which of the many health care professionals they had contact with to approach about their concerns. Lack of communication at an interdisciplinary level left them feeling that nobody was "joining the dots" for their health care. Conclusions: Patients with SLE do not feel understood by health care providers or people close to them. Support from trained volunteers with SLE, as available at the open access lupus clinic in Dudley (West Midlands, UK), would ensure more adequate information from someone with personal experience. Such services may improve communication and help minimise SLE patients' isolation.